Educational Adjustment Problems And Anxiety Level Of Adolescent Transitional Students From Self Financing To Government Schools In Kerala - Chandran R., Sarath (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Educational adjustment problems and anxiety are the two major psychological issues facing the students in their adolescent period. This study helps to find out the level of educational adjustment problems and anxiety level of adolescent transitional students from selffinancing to government schools in Kerala. In this study investigator defined the term transitional students as those who students undergo change their school in terms of curriculum. That is, from self- financing to Govt. Schools. Self-financing schools follows NCERT syllabus and rigid curriculum while Govt. Schools follows SCERT curriculum with constructivist approach. NCERT curriculum is more teacher-centered but SCERT curriculum is more student-centered. Purposive sampling technique was used in this study with sample size of three hundred (N=300) students from various districts of Kerala. In this study, the investigator administered Educational Adjustment Scale and anxiety scale for adolescent students those who undergo transition from self-financing to Govt. Schools. The present study reveals also that the relationship between educational adjustment problems and anxiety among adolescent transitional students from self-financing to Govt. schools.